Improving H2RG Performance in SPHEREx Brassboard Model - Chi H. Nguyen; Phillip Korngut; C. Darren Dowell; James Bock; Jill Burnham; Samuel Condon; Walter Cook; Grigory Heaton; Howard Hui; Branislav Kecman; Hiromasa Miyasaka; Kenneth Manatt; et al. (The Astrophysical Journal Supplement Series)
Spectro-Photometer for the History of the Universe, Epoch of Reionization, and Ices Explorer is an upcoming NASA satellite mission to study the physics of inflation, the history of galaxy formation, and the abundance of biogenic ices in the Milky Way, obtaining the first all-sky spectroscopic survey at infrared wavelengths 0.75–5.0 μ m. The instrument implements HAWAII-2RG (H2RG) detectors and custom-built Video8 electronics with multiple sampling features to optimize the H2RG noise performance, including nonsequential row reads, voltage monitoring, multiple visits to optically dark reference pixels, as well as onboard slope fitting and cosmic-ray removal. We report here the performance of a single H2RG with the readout electronics. We focus on the effectiveness of multiple reference samplings to reduce 1/ f noise most relevant to the galaxy formation analysis, in particular the noise on large angular scales k <0.13 [pix ^−1 ] (∼5″–20″) where the imprints of galaxy clustering will be measured. Our characterization confirms that increased sampling of reference pixels successfully reduces the 1/ f noise by ∼50% at these scales. However, the effectiveness of multiple reference reads is limited by irreducible per-pixel telegraph noise. Further noise reduction can be achieved by using optical pixels in addition to the reference pixels to remove common-mode signal offsets in each channel. Additionally, we observe that the gain of optical pixels is consistently ∼90% that of the reference pixels, prompting additional correction steps in the data reduction pipeline.